Future Directions and Concluding Remarks Navigating the Horizon of Software Quality Engineering - Pargaonkar, Shravan (Journal of Science & Technology, 2020)
In the ever-evolving landscape of technology, the trajectory of software quality engineering is a dynamic journey marked by innovation, challenges, and continual evolution. Coverage-based testing is the process of ensuring exercise of specific program elements. As we conclude our exploration into the realm of software quality engineering, it is essential to cast a speculative gaze into the future, discerning potential trends, emerging paradigms, and the transformative forces that will shape the discipline.